2019
DOI: 10.22578/ijms.17.3-4.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Flavonoid Fraction From Artemisia Annua in Comparison With Tacrolimus on Induced Atopic Dermatitis in Mice

Abstract: Background:Atopic dermatitis is a chronic inflammation of skin disease that is characterized by recurrent acute pruritus and dry skin. Mostly, atopic dermatitis is predominant in young children. The problems of increasing prevalence and high impact of disease on quality of patients and family's life, necessities identifying many atopic dermatitis prevention planes. Objective:To determine the effect of Artemisia annua flavonoids fraction in comparison with tacrolimus in atopic dermatitis like mice model. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Both norfloxacin ointment products were administered topically to the hand adjacent to the wrist in a 2 in. 2 area and inspected for any possible lesions, irritation, burning, or erythema. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both norfloxacin ointment products were administered topically to the hand adjacent to the wrist in a 2 in. 2 area and inspected for any possible lesions, irritation, burning, or erythema. …”
Section: Methodsmentioning
confidence: 99%
“…People suffering from psoriasis are more likely to have complications that are not limited to skin conditions. These encompass type 2 diabetes, obesity, coronary artery diseases, autoimmune diseases, and psychiatric issues. There is more evidence that psoriasis may arise simultaneously or consecutively with additional immune-mediated skin eruptions, most notably eczematous dermatitis. Research has also revealed links between psoriasis and an array of immune-associated conditions, among them ulcerated intestinal colitis. In addition, kidney impairment is known as one of the consequences of psoriasis. Moreover, arrays of drugs have been significantly implicated in the initiation and aggravation of psoriasis, namely, chloroquine, interferons, imiquimod, tetracyclines, and β-blocking agents …”
Section: Objective Of the Studymentioning
confidence: 99%
“…Coenzyme Q10-mediated reduction of ROS by activated PC-KUS leads to cessation of depigmentation and repigmentation [ 129 ]. In contrast, researchers in a randomised, single-blind, placebo-controlled trial in Iraq found a significant reduction in the Vitiligo Area Scoring Index after 8 weeks of topical gel application with CoQ10 [ 130 ].…”
Section: Potential Therapeutic Approaches To Reduce Oxidative Stressmentioning
confidence: 99%
“…Hydroquinone (ubiquinol), the reduced form of CoQ10, is a powerful lipophilic antioxidant that can recycle and regenerate other antioxidants like tocopherol and ascorbate. Co Q10 may protect cultured epidermal keratinocytes and dermal fibroblasts from the damaging effects of hydrogen peroxide and ultraviolet A (UVA) [21]. However, there were also reports of negative effects from using topical Co Q10.…”
Section: Skin Absorption and Dispersionmentioning
confidence: 99%